Blended Concessional Finance and COVID-19 - Sierra-Escalante, Kruskaia; Karlin, Arthur (International Finance Corporation, Washington, DC, 2021)
Blended concessional finance, the combination of commercial funds from development finance institutions (DFIs) and the private sector with concessional finance from public institutions, foundations, or other contributors, has become much more prominent in recent years as an effective method of spurring innovative private sector projects and programs in emerging markets. These concessional funds are being used in high-risk countries and for pioneering, innovative investments that can lead to dynamic growth and job creation and help meet the United Nations’ Sustainable Development Goals. In the wake of the COVID-19 pandemic, governments, development institutions, and private companies are trying to find mechanisms to prevent the loss of essential economic activity under difficult and uncertain market conditions. In this context, blended concessional finance deployed by DFIs is already playing an even greater role than in the recent past, as it can help bridge critical financing gaps by placing important projects within the risk tolerance of private sector investors and DFIs, despite great market and financial uncertainty. Blended concessional finance will play a critical role to ensure that the response to the pandemic remains focused on the most difficult markets and, as efforts to rebuild are put in motion, the rebuilding is done in an inclusive and climate and gender-smart manner.